Inertial force assessment in cross-country sit-skiers - Gastaldi, L.; Lisco, G.; Pastorelli, S. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of this study was to point out a biomechanical analysis of the poling cycle (PPG) achieved from CC sit-skiers to evaluate kinematics. In addition, starting from the analysis of the poling cycle performed from LW10 athletes, with no functional abdominals or extensors and no buttock sensibility, it has been observed how inertial effect due to the abrupt lowering of the arms may assure a propulsive force at the beginning of the PPG cycle.